Bracket/wire play: what to expect from tipping prescription on pre-adjusted appliances Folga braquete/fio: o que esperar da prescrição para inclinação nos aparelhos pré-ajustados - Leopoldino Capelozza Filho; Fabricio Monteiro de Castro Machado; Terumi Okada Ozawa; Arlete de Oliveira Cavassan; Mauricio de Almeida Cardoso (Dental Press Journal of Orthodontics, 2012)
INTRODUCTION: The opinion on the 'straight-wire' concept has been evolving since its origin, characterized by faithful followers or absolute skepticism. Currently, it seems reasonable to state that most professionals have a more realistic and critical viewpoint, with an attitude that reveals Orthodontics' maturity and greater knowledge on the technique. The most relevant criticisms refer to the impossibility of the both the Straight-Wire and the Standard systems to completely express the characteristics related to the brackets due to mechanical deficiencies, such as bracket/wire play. OBJECTIVES: A critical analysis of this relationship, which is unclear due to lack of studies, was the scope of this paper. METHODS: The compensatory treatment of two patients, using Capelozza's individualized brackets, works as the scenery for cephalometric evaluation of changes in incisor inclination produced by different dimensions of leveling archwires. RESULTS: The evaluation of these cases showed that, while the introduction of a 0.019 x 0.025-in stainless steel archwire in a 0.022 x 0.030-in slot did not produce significant changes in incisor inclination, the 0.021 x 0.025-in archwire was capable of changing it, mainly in mandibular incisors, and in the opposite direction to the compensation. CONCLUSION: Considering compensatory treatments, even when using an individualized prescription according to the malocclusion, the bracket/wire play seems to be a positive factor for malocclusion correction, without undesirable movements. Therefore, it seems reasonable to admit that, until a bracket system can have absolute individualization, the use of rectangular wires that still have a certain play with the bracket slot is advisable. INTRODUÇÃO: a opinião sobre o conceito Straight-Wire tem evoluído desde sua origem, caracterizada por seguidores fiéis ou ceticismo absoluto. Atualmente, parece razoável acreditar que a maioria dos profissionais tem uma visão mais realista e crítica, com uma postura que revela maturidade da Ortodontia e maior conhecimento sobre a técnica. As maiores críticas, e com fundamento, referem-se à impossibilidade do sistema, seja Straight-Wire ou Edgewise, expressar totalmente as características embutidas nos braquetes, devido a deficiências mecânicas como folga entre braquetes e fios. OBJETIVOS: uma análise crítica dessa relação mal explicada, pela carência de estudos, foi o escopo desse artigo. MÉTODOS: o tratamento compensatório de dois pacientes, realizados com braquetes individualizados Capelozza, serve de cenário para uma avaliação cefalométrica das alterações nas inclinações dos incisivos produzidas por diferentes calibres de arcos de nivelamento. Resultados: a avaliação dos casos mostrou que, enquanto a introdução do arco de nivelamento de aço 0,019" X 0,025" em canaleta 0,022" X 0,030" não produziu alterações significativas nas inclinações dos incisivos, o arco 0,021" X 0,025"foi capaz de alterá-las, principalmente nos incisivos inferiores, e em direção contrária ao sentido da compensação. CONCLUSÃO: em tratamentos compensatórios, mesmo buscando-se utilizar prescrição individualizada de acordo com a má oclusão, a folga entre braquete e fio parece ser um fator positivo para que ocorra a correção da oclusão, sem que movimentos indesejáveis aconteçam. Assim, parece razoável admitir que, até que um sistema de braquetes permita ter uma individualização absoluta, é recomendável a utilização de fios retangulares que preservem uma folga com a canaleta do braquete.